2003
DOI: 10.1002/malq.200310048
|View full text |Cite
|
Sign up to set email alerts
|

Choice principles for special subsets of the real line

Abstract: We study the role the axiom of choice plays in the existence of some special subsets of R and its power set ℘(R).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Truss [29, Theorem 3]. From the above considerations, it follows that neither (#) is provable in ZF$\mathsf {ZF}$.Finally, we point out that it is an open problem whether or not sans-serifACfalse(sans-serifPdouble-struckRfalse)$\mathsf {AC}(\mathsf {P}\mathbb {R})$ is equivalent to sans-serifACfalse(double-struckRfalse)$\mathsf {AC}(\mathbb {R})$ in ZF$\mathsf {ZF}$; for a partial (non‐trivial) solution to this open problem, the reader is referred to Keremedis and Tachtsis [18, § 5]. Let (##) stand for the following weaker form of the Hewitt–Marczewski–Pondiczery Theorem:(##) A non‐empty product of 20$\le 2^{\aleph _{0}}$ separable Hausdorff spaces, each with at least two points, is separable.We have the following implications:To see that (a) is true, fix a continuum sized family scriptA=false{Ai:idouble-struckRfalse}$\mathcal {A}=\lbrace A_{i}:i\in \mathbb {R}\rbrace$ of non‐empty subsets of R$ \mathbb {R}$.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Truss [29, Theorem 3]. From the above considerations, it follows that neither (#) is provable in ZF$\mathsf {ZF}$.Finally, we point out that it is an open problem whether or not sans-serifACfalse(sans-serifPdouble-struckRfalse)$\mathsf {AC}(\mathsf {P}\mathbb {R})$ is equivalent to sans-serifACfalse(double-struckRfalse)$\mathsf {AC}(\mathbb {R})$ in ZF$\mathsf {ZF}$; for a partial (non‐trivial) solution to this open problem, the reader is referred to Keremedis and Tachtsis [18, § 5]. Let (##) stand for the following weaker form of the Hewitt–Marczewski–Pondiczery Theorem:(##) A non‐empty product of 20$\le 2^{\aleph _{0}}$ separable Hausdorff spaces, each with at least two points, is separable.We have the following implications:To see that (a) is true, fix a continuum sized family scriptA=false{Ai:idouble-struckRfalse}$\mathcal {A}=\lbrace A_{i}:i\in \mathbb {R}\rbrace$ of non‐empty subsets of R$ \mathbb {R}$.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we point out that it is an open problem whether or not sans-serifACfalse(sans-serifPdouble-struckRfalse)$\mathsf {AC}(\mathsf {P}\mathbb {R})$ is equivalent to sans-serifACfalse(double-struckRfalse)$\mathsf {AC}(\mathbb {R})$ in ZF$\mathsf {ZF}$; for a partial (non‐trivial) solution to this open problem, the reader is referred to Keremedis and Tachtsis [18, § 5].…”
Section: Resultsmentioning
confidence: 99%
“…(12) In [21] it is shown that Form 212 does not imply either of AC(R), Form 203, and in [10] it is shown that Form 212 does not imply Form 368. (13) In [10] we showed that Form 368 is true in M1. Since (14) Tarski [19] has shown that Form 368 implies Form 170.…”
mentioning
confidence: 99%